The residential real estate market in Poland - Siemińska, Ewa (Business: Theory and Practice, 2012)
The paper presents the functioning of the Polish residential real estate market from the perspective of the construction and financial sectors. Developers operating on a dynamic market must respond quickly and flexibly to the changes occurring on the market, e.g., at the growth stage they should be increasing their investment portfolios, while during the slowdown stage they should be taking measures to maintain the scale of their business, or be reducing the price of the developed area. The paper also shows the involvement of the banking sector in financing the real estate market, which affects majorly the dynamics of the real estate market development.